Digital Analysis Methods in Business-Processes and Projects in Digital Twins at Investment-Construction Companies - A. I. Sukhorukov; E. A. Zakharova; E. V. Shvetsov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article analyzes modeling of investment-construction company work from graph models to digital analogues. Such analysis is necessary in order to build economically grounded twin of the investment-construction company. The need to use advanced digital methods of business-analysis in conditions of real time was substantiated. It was demonstrated that elaboration of digital methods of business-analysis in projects and business-processes in investment-construction work is acute and leans against numerous factors. They are as follows: positive overseas experience in projecting and controlling processes; adjustment of this experience to specific features of project and business-process organization in Russia; use of digital imitation models of investment-construction enterprise in conditions of real time; introduction of digital methods of strategic and operative business-analysis of projects and business-processes into imitation model and digital twins at investment-construction enterprises; use of promising digital technologies in digital methods of business-analysis in projects and business-processes, for instance, analysis of big data, artificial neuron nets, cloud technologies, internet of things, virtual reality, augmented reality, technologies of register distribution, automation and robotics of business-processes, etc. Typical features of digital analysis built in digital twin for effective decision-making in management were identified. The article provided results of modeling visualization and digital analysis of business-processes.